Effect of workload, job promotion, and work motivation on employee performance in PT XYZ - Rezka Lukman Nul Hakim; Alnisa Min Fadlillah (Journal of Research in Business, Economics, and Education, 2021)
This study is a quantitative study that aims to determine the effect of workload, promotion, and motivation on employee performance PT XYZ. This study uses a sample size of 57 respondents who are employees of PT XYZ. The analysis technique in this study is to use the Coefficient of Determination Test, t-test (partial) and F-test (simultaneous) using Smart PLS 3.0 software. The test results show that (1) workload has a significant effect on employee performance at PT XYZ, (2) promotion has a significant effect on employee performance at PT XYZ, (3) work motivation has a significant effect on employee performance at PT XYZ, (4) workload, promotion, and work motivation have a significant effect on employee performance of PT XYZ.